Immediate postpartum IUD: analysis of factors making it contraceptive of choice - Trivedi, Anshuli; Kasar, P. K.; Tiwari, Rajesh; Sharma, Arvind (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Intrauterine devices are convenient, long term, reversible means of contraceptive. They are user friendly due to one-time application, ease of removal and immediate return of fertility on its removal. The Immediate Postpartum IUD is inserted in women within 48 hours, after normal delivery. The study aims to understand factors responsible for making IUD as the contraceptive of choice. It also identifies various social, demographic factors responsible for making IUD as the contraceptive of choice. Methods: A cross-sectional observational study was done using pretested questionnaire. In total 470 subjects were interviewed. The data were collected and compiled using MS-excel and analyzed by using Epi info-7. Data is presented in terms of proportions. Results: The acceptance of IUD as a contraceptive was not statistically associated with age & income of the user. Acceptance for IUD increased with literacy (P = 0.003). Almost 77.8% users were satisfied by the IUD. In total, 66.68% users, who continued using IUD did not feel any discomfort. The compliance of IUD was significantly associated with the discomfort caused (P = 0.0008) which was found to be most important reason for its removal. The commonest reason for adoption of IUD was a long duration of its use. It was seen that 23.40% previous contraceptive users and 39.41% new IUD users accepted it as contraceptive. Its acceptance is especially more in previous IUD users. Conclusions: Immediate post-partum IUCD has high acceptability and more than 75% users are satisfied and consider it as a contraceptive option.